2018
DOI: 10.1001/jamapediatrics.2018.1323
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of Rituximab vs Tacrolimus in Pediatric Corticosteroid-Dependent Nephrotic Syndrome

Abstract: IMPORTANCE Calcineurin inhibitors are an established first-line corticosteroid-sparing therapy for patients with corticosteroid-dependent nephrotic syndrome (CDNS), whereas B-lymphocyte-depleting therapy is mostly used as a rescue for calcineurin inhibitor-resistant cases. The positive efficacy and safety profile of rituximab raises the question of whether it could be used as a first-line alternative to calcineurin inhibitor therapy. OBJECTIVE To compare the efficacy of rituximab and tacrolimus in maintaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
109
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(120 citation statements)
references
References 31 publications
6
109
0
5
Order By: Relevance
“…To date, only two major reports have assessed the use of rituximab in early-stage uncomplicated SDNS. Ravani et al conducted a multicenter, open-label, randomized, control trial [10] and Basu et al conducted a single-center, parallel-arm, open-label, randomized, clinical trial [11]. Compared with these previous reports, our trial is of high quality as clinical research.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…To date, only two major reports have assessed the use of rituximab in early-stage uncomplicated SDNS. Ravani et al conducted a multicenter, open-label, randomized, control trial [10] and Basu et al conducted a single-center, parallel-arm, open-label, randomized, clinical trial [11]. Compared with these previous reports, our trial is of high quality as clinical research.…”
Section: Discussionmentioning
confidence: 95%
“…The results from this trial indicated that rituximab allows the complete withdrawal of steroids in patients with childhood SDNS without adversely affecting clinical outcomes and that the drug has an acceptable short-term adverse event profile [10]. One clinical trial indicated that rituximab is more effective than tacrolimus over a 12-month period in maintaining disease remission and minimizing corticosteroid exposure [11]. Despite these results, additional data are needed to inform clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Basu et al conducted an open label randomized clinical trial in India where 120 children with non-complicated courses of SDNS were randomized to receive either tacrolimus for 12 months combined with tapering alternate-day prednisolone or 2–4 weekly infusions of rituximab (375 mg/m2) (43). Frequency of infusions was guided by depletion of B cell count and since all children achieved adequate B cell depletion after the second dose of rituximab, all children received only 2 doses.…”
Section: Effectiveness Of Rituximab In Sdns and Frnsmentioning
confidence: 99%
“…In recent years, rituximab (RTX) has generally been used in the treatment of patients with PSL-and/or CsA-dependent FRNS, particularly for children [12]. RTX may therefore be considered as the first-line immunosuppressive drug for children.…”
Section: Discussionmentioning
confidence: 99%